An analysis of the bid behavior of the 2005 JCDL program committee - Rodriguez, Marko A.; Bollen, Johan; Van de Sompel, Hebert (International Conference on Digital Libraries: Proceedings of the 6th ACM/IEEE-CS joint conference on Digital libraries; 11-15 June 2006, 2006)
This article presents an analysis of the bid behavior of the 2005 JCDL program committee. For each paper, poster, and tutorial submitted for review to the 2005 JCDL, each program committee member was asked to state their expertise with regards to the subject domain of the submission. We present the various statistical techniques used throughout this study with sufficient diagrams to ensure that the audience understands the methods and conclusions drawn from the study